PENERAPAN DISC MODUL UNTUK MENINGKATKAN KREATIVITAS PEMBELAJARAN MATEMATIKA SISWA KELAS V SEKOLAH DASAR - Herry Agus Susanto Herry Agus Susanto; Fitriana Fitriana (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2014)
Abstract: Implementing of disc module for improving mathematic learning creativity of fifth grade elementary school students. Purpose of the research was to describe improvement students creativity through disc module on mathematic teaching integer number at fifth grade Gentang Elementary School Bendosari, Sukoharjo, Type of the research was classroom action research (CAR) which was conducted in two cycles. Data collection methods were observation, interview, and test. Research results showed: (1) Teaching discmodule integer number material improved students’ creativity, and (2) improved students student’ learning achievement.Keywords: disc module, creativity, learning achievement, elementary school studentsAbstrak: Tujuan penelitian ini adalah mendeskripsikan peningkatan kreativitas siswa melalui Disc Modul pada pembelajaran matematika materi bilangan bulat pada kelas V SD Gentan Bendosari Sukoharjo. Jenis penelitian adalah penelitian tindakan kelas (PTK), yang dilaksanakan sebanyak dua siklus. Pengumpulan data menggunakan teknik observasi, wawancara, dan tes. Hasil penelitian menunjukkan: (1) pembelajaran disc modul materi bilangan bulat dapat meningkatkan kreativitas siswa, dan (2) meningkatkan hasil belajar siswa. Kata Kunci: disc modul, kreativitas, hasil belajar, siswa SD